Workforce Training in the Thatcher Era: Market Forces and Market Failures. - Greenhalgh, C; Mavrotas, G (1993)
Summarizes changing employment patterns. Documents the rising incidence of vocational training for the economically active adult workforce, using data from successive Labour Force Surveys, and considers the issue of positive externalities arising from worker mobility.